ECMAN A Standard Database Management System for Electronic Chart Display and Information Systems (ECDIS) - Astle, H.; van Opstal, L. H. (The International Hydrographic Review, 2015)
Electronic Charting made its debut over 10 years ago in the Canadian Arctic. At that time, its applications were limited to keeping a ship in the centre of a very narrow, ice filled channel. Today, electronic charting is viewed by some as being an answer to many of the major concerns of the shipping industry. Electronic charts can provide the information, currently available in the various formats and locations on the bridge, in a single integrated display system. To do so, this information must be accessible and properly managed. This paper reviews Universal Systems’ solution to the data management requirements of electronic charting.